Study of physico-chemical properties of biopolymers chitin-chitosan synthesized from poddle bees Apis Mellifera - Nurutdinova Feruza; Tuksanova Zebiniso; Rasulova Yulduz (E3S Web of Conferences, 2024)
The article presents the optimal method for the synthesis of chitin polymers - chitosan from dry dead bees. In the experiment, the first deproteinization process was carried out, which was carried out in two stages by treating crushed dead bees with 0.5 N sodium hydroxide solution for 1 hour at 100 0C using the chitinase enzyme. At the second stage, by treating dead bees with a 2 M hydrochloric acid solution for 5 hours at room temperature according to the Hackman method, a demineralization reaction was carried out and a chitin polymer was obtained. demineralization was carried out on the basis of 2-normal hydrochloric acid from dead bees. When chitin was deacetylated with a 35% NaOH aqueous solution for 1.5 hours at a temperature of 85 0C and dried at 50-55 0C, chitosan was obtained. Study of the physicochemical properties of chitosan. Methods for determining the molecular weight, viscosity, moisture content, degree of deacetylation, and nitrogen content in polymers are presented. When determining the constants, the optimal media were chosen.